BBGKY hierarchy and its evolution operator for one class of integrable systems - Skrypnik, W. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We define the abstract BBGKY hierarchy and its formal evolution operator. The existence of the latter is established in a special Banach space for a system of charged particles with Chern-Simons interaction regularized for small and large distances. An analog of the high-temperature expansion of equilibrium statistical mechanics is applied.